2016
DOI: 10.1063/1.4959595
|View full text |Cite
|
Sign up to set email alerts
|

Growth and device processing of hexagonal boron nitride epilayers for thermal neutron and deep ultraviolet detectors

Abstract: Solid-state neutron detectors with high performance are highly sought after for the detection of fissile materials. However, direct-conversion neutron detectors based on semiconductors with a measureable efficiency have not been realized. We report here the first successful demonstration of a direct-conversion semiconductor neutron detector with an overall detection efficiency for thermal neutrons of 4% and a charge collection efficiency as high as 83%. The detector is based on a 2.7 μm thick 10B-enriched hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…Table II summarizes the performance of semiconductor based solar-blind PDs. 88,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] The table is ordered by the use of different groups of materials. As indicated in the table, III-nitride based PDs are among the first and ideal choices for high efficiency and high-speed devices.…”
Section: Detectorsmentioning
confidence: 99%
“…Table II summarizes the performance of semiconductor based solar-blind PDs. 88,[96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] The table is ordered by the use of different groups of materials. As indicated in the table, III-nitride based PDs are among the first and ideal choices for high efficiency and high-speed devices.…”
Section: Detectorsmentioning
confidence: 99%
“…7(a). [9][10][11] The system design was adopted from the thesis work of Clinton 17,30 and based on a depleted sealed source, model 100 californium-252 source ( 252 Cf) which contained 4.2 lg of active 252 Cf from Frontier Technology, emitting fission neutrons, moderated by a high density polyethylene (HDPE) block. The experimental geometry and HDPE size and thickness are identical to those described in the thesis.…”
Section: Vlsmentioning
confidence: 99%
“…It is important to point out that the BN interaction with gamma photons is exceptionally low due to the fact that BN is composed of low atomic number elements. 9,11 Our previous measurement results have demonstrated that h-BN detectors have a negligible response to c-photons produced by 137 Cs decay with an energy at 0.662 MeV and possess a neutron-gamma rejection ratio larger than 10 6 . 9,11 Corroborating with the leakage current and ls-product results, the measured neutron detection efficiency results also indicate that one of the prominent effects on the detector performance is the choice of ohmic contact material and that the Ni/Au bilayer is the preferred choice over the Ti/Al bilayer.…”
Section: Vlsmentioning
confidence: 99%
See 2 more Smart Citations